∫ − 4 π 4 π e sin 3 x + 1 cos x d x
Find the value of the integral above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I = ∫ − 4 π 4 π e sin 3 x + 1 cos x d x = ∫ − 2 1 2 1 e u 3 + 1 1 d u = ∫ − 2 1 2 1 e u 3 + 1 e u 3 + 1 − e u 3 d u = ∫ − 2 1 2 1 d u − ∫ − 2 1 2 1 e u 3 + 1 e u 3 d u = 2 2 − ∫ − 2 1 2 1 1 + e − u 3 1 d u = 2 2 − ∫ − 2 1 2 1 1 + e t 3 1 d t = 2 2 − I = 2 1 ≈ 0 . 7 0 7 Let u = sin x ⟹ d u = cos x d x Let t = − u ⟹ d t = − d u
You worked too hard. :D
Problem Loading...
Note Loading...
Set Loading...
We can always apply the following formula: ∫ − a a f ( t ) d t = ∫ 0 a ( f ( t ) + f ( − t ) ) d t
Doing so with our integral gives ∫ − 4 π 4 π e sin 3 x + 1 cos x d x = ∫ 0 4 π ( e sin 3 x + 1 cos x + e − sin 3 x + 1 cos x ) d x = ∫ 0 4 π ( e sin 3 x + 1 cos x + 1 + e sin 3 x cos x e sin 3 x ) d x = ∫ 0 4 π e sin 3 x + 1 cos x ( e sin 3 x + 1 ) d x = ∫ 0 4 π cos x d x = sin 4 π − sin 0 = 2 2 ≈ 0 . 7 0 7 1